Challenges in Assessing the Cost-Effectiveness of Newborn Screening: The Example of Congenital Adrenal Hyperplasia - Scott D. Grosse; Guy Van Vliet (International Journal of Neonatal Screening, 2020)
Generalizing about the cost-effectiveness of newborn screening (NBS) is difficult due to the heterogeneity of disorders included in NBS panels, along with data limitations. Furthermore, it is unclear to what extent evidence about cost-effectiveness should influence decisions to screen for specific disorders. Screening newborns for congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency can serve as a useful test case, since there is no global consensus on whether CAH should be part of NBS panels. Published and unpublished cost-effectiveness analyses of CAH screening have yielded mixed findings, largely due to differences in methods and data sources for estimating health outcomes and associated costs of early versus late diagnosis as well as between-country differences. Understanding these methodological challenges can help inform future analyses and could also help interested policymakers interpret the results of economic evaluations.